DNA-free transcriptional activation of cabbage (Brassica oleracea L.) using CRISPR/DCAS9 ribonucleoproteins to enhance heat stress tolerance based on morphophysiological plant traits - Moradpour, Mahdi (2021)
Red cabbage (B. oleracea) is one of the most distinct species among the numerous species of Brassica genus due to having high level of anthocyanins. Brassica species are widely consumed vegetable crops with great health benefits. However, they are highly vulnerable to high temperature and their production are limited to highland areas in Malaysia. Understanding how plants adjust their developmental programs in response to temperature variations is central to sustain crop productivity in the modern agriculture facing global climate change. Global climate change has generated significant fluctuations of ambient growth temperature, which can profoundly influence diverse developmental, physiological, and morphological responses, including modulations in plant growth and yield. In recent years, many crop genomes have been sequenced and innovative biotechnological approaches allowed to take a step forward towards the development of new improved cultivars harboring precise genome modifications. Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 system, represents the main methods available for plant genome engineering through targeted modifications. Such technology, however, requires efficient transformation protocols and extensive genomic resources and accurate knowledge before they can be efficiently exploited in practical breeding programs. This study investigated on heat-tolerant/sensitive cultivars based on morphophysiological indicators and the action and interaction of different genes in the molecular network to serve as critical tools for genetic improvement in cabbage. The feasibility of DNA-free transcriptional activation method through delivery of CRISPR/dCas9-based transcriptional activation domains (TADs) ribonucleoproteins (RNPs) into the red cabbage protoplasts was also evaluated. To screen the morphophysiological indicators, the morphological and physiological performance of two different varieties of white and red cabbages (B. oleracea var. capitate f. alba and f. rubra, respectively) under heat stress (HS) at 42°C for 5h and non-stress (NS) was evaluated. Cultivars that showed considerable cell membrane thermostability and less reduction on chlorophyll content with better head formation were categorized as the heat tolerant cultivars (HTC). While those with reduction in stomatal conductance and higher reduction incurred on chlorophyll and damage on thylakoid membranes as the heat sensitive cultivars (HSC). In order to select the target genes, the expression of four key genes in cabbage HS response pathway were evaluated in HTCs and HSCs as determined by morphophysiological indicators. Expression profiles of key genes in HS response network including BoHSP70 (HEAT SHOCK PROTEIN 70), BoSCL13 (SCARECROW-LIKE 13), BoDPB3 (transcriptional regulator DNA POLYMERASE II SUBUNIT B3 (DPB3))/NUCLEAR FACTOR Y SUBUNIT C10 (NF-YC10) evaluated in all cultivars under HS at 42ºC for 3h and 5h compared to NS. Based on the results, the morphophysiological and molecular indicators are applicable to cabbage cultivars for differentiating HTC and HSC and potential target genes for genome editing identified for enhancing food security in the warmer world. The results of expression profiling of these key genes in HS response network indicated that in order to increase tolerance of red cabbage to HS, BoDPB3, is a potential target gene for activation. A versatile protoplast system for delivery of RNPs composed of purified dCas9 fusion proteins fused to transcriptional activation domain (VP64) and four different in vitro transcribed (IVT) single guide RNAs (sgRNAs) using PEG into the red cabbage protoplasts was successfully established. The highest endogenous gene activation was 15.7-fold using RNP 3, for BoDPB3 whereas RNP 3 and RNP1 modestly activated BoDPB3 by 6.7-fold and by 4.6-fold, respectively indicating that the closer position of the sgRNAs targeting antisense and sense strands of BoDPB3 promoter region to the transcriptional start site gave higher expression. The interaction of targeted HS responsive gene activation by CRISPR/dCas9-VP64-RNPs within HS regulatory network in red cabbage was also evaluated. The results showed that the dCas9-VP64 tool was capable to regulate transcriptional regulatory network of HS response genes through enhancing the expression BoDPB3 by 15.7-fold which consequently led to significant suppression of the expression level of BoDRIP by 13.3-fold. Our study demonstrated that CRISPR/(d)Cas9-TAD RNPs is a potential tool for targeted gene activation, while avoiding the undesirable integration effects of plasmid DNA in the host genome. The CRISPR/(d)Cas9-TAD RNPs could be a valuable system for facilitating plant researchers in interrogating gene functions and for manipulating biological traits. Two HTC showed better head formation compared to cabbages from HSC. One HTC (WCC1) and two HSC (WCC3 and RCC) were selected to study the effects of HS on expression profiles of key genes in HS response network. Strong induced expression of HEAT SHOCK PROTEIN 70 (BoHSP70) was observed for all three cultivars under HS (RCC by 70.7-fold, WCC1 by 23.5-fold and WCC4 by 15.70-fold) compared to non-stress (NS) plants. BoSCL13 which showed strong induced expression in WCC1 by 14.4-fold but not in WCC3 under HS can be used to differentiate HTC from HSC in green cabbage cultivars. BoDPB3, a DEHYDRATION RESPONSIVE ELEMENT BINDING PROTEIN 2A (DREB2A) interactor showed suppressed expression in RCC by 0.3-fold unlike WCC1 by 4.3-fold and WCC3 by 3.5-fold that demonstrated enhanced expression under HS, explaining the high sensitivity of RCC to HS.